Right–left propensity of cardiogenic cerebral embolism in standard versus bovine aortic arch variant. Issue 3 (25th January 2018) - Gold, Menachem; Khamesi, Mojdeh; Sivakumar, Mangaiyarkkarasi; Natarajan, Vijaya; Motahari, Hooman; Caputo, Nicholas
Abstract : Left‐hemispheric ischemic strokes are more frequent overall and often have a worse outcome than their right‐hemispheric counterparts. We hypothesized that the right‐left propensity of CE cerebral infarcts differs between patients with standard and bovine arch variants. We retrospectively identified all patients with acute stroke of the anterior circulation admitted to our primary stroke center between January 2011 and June 2017 who had moderate‐ to high‐risk cardio‐embolic sources according to the SSS‐TOAST classification. From amongst these patients, only those with available cross‐sectional imaging of the aortic arch were included. Lesion side and patterns on diffusion‐weighted magnetic resonance imaging were determined blinded to the aortic arch imaging. One hundred and nineteen patients met the TOAST criteria for moderate‐ or high‐risk cardio‐embolic source. Of these, 58 (49%) were men and the median age was 71.9 years; 33% of the patients had a bovine arch. The most common etiologies of CE were atrial fibrillation ( n  = 80 [67%]) and congestive heart failure with ejection fraction <30% ( n  = 18 [15%]). In patients with bovine arch there was an approximately 50% chance of having a right‐ or left‐sided infarct. Although there was a trend towards right‐sided lesions in patients with standard arches, this did not reach statistical significance. No statistically significant difference in embolic stroke laterality was demonstrated in our relatively small sample. Bovine arch could be an independent risk factor for cardio‐embolic embolism. Clin. Anat. 31:310–313, 2018. © 2018 Wiley Periodicals, Inc.